Moonlight Ritual: An ethnobotanical study of the purnama ceremony in the hindu community of malang - Mustikasari, Ayu Chandra; Kharisma, Nafi' Windy; Firdausya, Syifa Nabila; Putra, Ade Fandy Ardiyansyah; Muhaimin, Fahrul Ghani; Mahanal, Susriyati (STKIP Persada Khatulistiwa Sintang, 2026)
Indonesia’s biodiversity and culture are interconnected through local knowledge that is increasingly threatened by modernization. This study aims to document local knowledge related to plant use in the Purnama ceremony of the Hindu community in Wagir District, Malang Regency, East Java. This research employed a descriptive qualitative approach. Informants were selected using purposive and snowball sampling. Data were collected through interviews, observations, and documentation. The results identified 24 plant species from 22 families used in ritual offerings. The findings highlight plant diversity, plant parts used, philosophical meanings, and conservation efforts. Most species were used in fresh form and were classified as Least Concern based on IUCN data. These results indicate that the Purnama ceremony supports the preservation of local knowledge and culturally based biodiversity conservation.